2000
DOI: 10.1177/0145482x0009400204
|View full text |Cite
|
Sign up to set email alerts
|

Sensorial Afferents and Center of Foot Pressure in Blind and Sighted Adults

Abstract: Variations in body posture were evaluated in 19 blind and 19 sighted adults by changes in the subjects’ center of foot pressure on a force plate in time in three positions. The subjects who were blind had significantly larger body sway than did the sighted subjects in all trials except those in the sound position, where they had a better control of their stance than did the sighted subjects, and their body oscillations were also reduced in the forward-looking position. Thus, sound or proprioceptive adjunctive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…2). This finding is in accordance with those of previous studies when momentary loss of vision resulted in increased body sway (Schieppati et al 1999;Schmid et al 2007;Sforza et al 2000). Interestingly, blind individuals in our study demonstrated lower balance control in A/P direction compared to sighted participants when they performed the balance tests blindfolded, but the increased sway in blind individuals compared to sighted individuals with eyes closed was abolished in M/L axis (Fig.…”
Section: Static Balance Controlsupporting
confidence: 93%
See 1 more Smart Citation
“…2). This finding is in accordance with those of previous studies when momentary loss of vision resulted in increased body sway (Schieppati et al 1999;Schmid et al 2007;Sforza et al 2000). Interestingly, blind individuals in our study demonstrated lower balance control in A/P direction compared to sighted participants when they performed the balance tests blindfolded, but the increased sway in blind individuals compared to sighted individuals with eyes closed was abolished in M/L axis (Fig.…”
Section: Static Balance Controlsupporting
confidence: 93%
“…Earlier studies have reported that vision plays a major role in postural control and that postural sway increases in the absence of vision (Choy et al 2003;Hsu et al 2007). Visually impaired humans, especially those who have never received any visual stimulation, often exhibit poor static and dynamic balance (Easton et al 1998;PortforsYeomans and Riach 1995;Schmid et al 2007;Sforza et al 2000) and display an increased risk of falling (Aydog et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Under such conditions, an immediate increase in the range of COP swaying occurs in individuals without visual impairment (Schieppati, Tacchini, Nardone, Tarantola, & Corna, 1999;Schmid et al, 2007;Sforza et al, 2000). Decreased values of AP, ML, and SA COP were observed during the closed eye measurement in group E; these findings should be interpreted as an increase in postural stability.…”
Section: Discussionmentioning
confidence: 86%
“…Numerous previous studies documented that blind individuals are characterized by a lower level of postural stability, manifested by increased area of COP swaying in coronal and sagittal planes (Blomqvist & Rehn, 2007;Easton, Greene, Dizio, & Lackner, 1998;Schmid, Nardone, De Nunzio, Schmid, & Schieppati, 2007;Sforza et al, 2000). According to Rauschecker (1995) and Schmid et al (2007), greater COP sways result from the lack of interaction between visual stimuli and motor behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation